2011
DOI: 10.3892/or.2011.1281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes related to carcinogenesis of oral leukoplakia by oligo cancer microarray analysis

Abstract: Abstract. the aim of this study was to identify genes that are predictive of carcinogenic change in patients of oral leukoplakia (olK) using a cancer-related microarray. candidate biomarkers were discovered using the oligo geArray oHs-802 and validated on independent samples by semi-quantitative reverse transcription-pcr (rt-pcr) and real-time rt-pcr. Both the discovery and the validation cohorts of samples included normal oral tissues, olK tissues and oral squamous cell carcinoma (oscc) tissues. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Kondoh et al identified 11 genes that distinguished oral SCC from leukoplakia with greater than 97% accuracy 89 . Another group identified a panel of 9 genes that differentiated normal mucosa, oral leukoplakia, and invasive carcinoma 62 . The results of each of these studies differ, likely due to differences in patient selection, tumor heterogeneity, and the use of different microarray platforms.…”
Section: Altered Gene Expression Profilesmentioning
confidence: 99%
“…Kondoh et al identified 11 genes that distinguished oral SCC from leukoplakia with greater than 97% accuracy 89 . Another group identified a panel of 9 genes that differentiated normal mucosa, oral leukoplakia, and invasive carcinoma 62 . The results of each of these studies differ, likely due to differences in patient selection, tumor heterogeneity, and the use of different microarray platforms.…”
Section: Altered Gene Expression Profilesmentioning
confidence: 99%